THE ROLE OF WOMEN AND YOUTH IN NATIONAL DEVELOPMENT - Za'faran Hassan 626552; Zarina Abu Bakar, editor 653159; Abdul Halim Sidek, editor 292785; Zuraidah Musib, editor 653190; Sulaiman Mohd. Nor 269497; Rose Halim, editor 653188 (Shah Alam : University Publication Centre, UPENA, UiTM, 2010)
The topic of the Tenth Perdana Discourse Series' keynote address by Tun Dr. Mahathir Mohamad is, The Role of Women and Youth in National Development. He divided his speech into twoparts:women and youth. He began by talking about the population of women and men in Malaysia. He touched briefly on the topic of polygamy and then elaborated on the subject of women who tend to work harder and become more independent than men. Women are better able to acquire knowledge and skills compared to men; as a result, there are now more women than men studying in universities and colleges. Next, he talked about the role of youth in national development, and admitted that youth nowadays are more intelligent and can contribute many ideas for the development of this country. Dr. Mahathir said that youths must acquire knowledge and skills and must have the necessary qualifications to prepare them to lead other youths and the nation.